A large area timing RPC - Blanco, A. (2002)
A large area Resistive Plate Chamber (RPC) with a total active surface of 160×10 cm2 was built and tested. The surface was segmented in two 5 cm wide strips readout on both ends with custom, very high frequency, front-end electronics.